O português escrito no facebook: uma descrição dos marcadores conversacionais - FRAZÃO, Elisiane Araújo dos Santos (2018)
The global computer network maximized the extent of interactions, which today are independent of physical presence and a shared time space, then can be mediated by the digital media, based on the old practices of face-to-face conversation. The present work intentions to investigate the Portuguese Language written on Facebook, seeking to understand the conversational markers as linguistic phenomena in use and identifying the functions performed by them in the sewing and the construction of meaning of the discourses produced in the digital interaction. As a theoretical contribution, we used the studies of authors such as Marcuschi (1986, 2004, 2007), Castells (2005), Castilho (1989, 2010, 2014), Hilgert (2000), Crystal (2001, 2005), Shepherd and Saliés (2013), Recuero (2008, 2014), Barton and Lee (2015), Santos (1997, 2006), Urbano (1993), Xavier (2013a, 2013b), Among others theorists who discuss the relationship between society, technology and communication, and that it is important to understand the relationship between society, technology, and communication made possible the unveiling of our research phenomenon. The methodological procedures are based on the Hermeneutic Phenomenology of Paul Ricoeur (1989, 1991, 1996) and, for data collection, we chose to construct a corpus composed of texts / speeches captured from the Facebook Profile page. For the analysis of the data, we are guided by the following guiding question: How are conversational markers manifested in texts written on Facebook? Among the constructed corpus texts, only 7 (seven) were selected for analysis. After having reflected, we tried to demonstrate that the conversational markers, typical elements of the face-to-face conversation, are also used in the digital conversation, organizing the sewing of the interactions and also demonstrating the flexibility of the language to the contextual influences historical, social and technological. The results point out that the linguistic achievements produced by Facebook interactors are affected by the immediate context, revealing a written code reinvented to favor communication and evidencing the need to see the differences between speech and writing from the viewpoint of the uses of the language production situations.